PELATIHAN PEMBUKUAN DENGAN APLIKASI BUKU WARUNG BAGI UMKM GUNA MEMAKSIMALKAN KEUANGAN - Rachayu Aulia NurHepita; Nurma Risa; Ari Dewi Cahyati (Universitas Islam 45 Bekasi, 2022)
In the IT and Web of Thinks (IoT) based period, which is used by humans, an application is on Android that can be accessed anywhere and becomes a person's need. This bookkeeping application on Android can be accessed as a recording tool for money entry or exit that can be accessed easily and can be applied as small or medium business actors and above. The role of MSME actors in RT 012, Duren Jaya is a trader from various circles. Every type of business carried out has a very relative turnover, so it requires a tool that can help financial records. For now, there are still many MSME actors who still do it by manual recording and still don't use technology, they still use manual recording in books to record their finances. The method that will be implemented in this activity is the bookkeeping training method for SMEs. So that this activity can be carried out properly so that residents can take advantage of technology-based financial bookkeeping applications, making it easier for recording and facilitating the development of the business being carried out.